2021
DOI: 10.1029/2021ef002275
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Cyclone Frequency

Abstract: Tropical cyclone frequency is the number of tropical cyclones occurring over a given time period and spatial domain. Here, we are most interested in the annual frequency over either the entire globe or individual basins, that is, particular distinct portions of the tropical oceans over which tropical cyclones occur (such as the North Atlantic, South Indian, etc.). Tropical cyclone frequency strongly controls the total hazard and risk from tropical cyclones, because no other aspect of a tropical cyclone matters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 188 publications
(276 reference statements)
4
70
0
1
Order By: Relevance
“…This disagreement in projected changes between models highlights the importance of considering projections from a model ensemble rather than a single model. In addition, even if more of the cyclones that form in the future are more intense, the overall frequency of cyclones is most often predicted to stay the same or drop (Sobel et al., 2021). This means that the absolute frequency of intense cyclones may not rise, depending on how much overall cyclone frequency changes.…”
Section: Discussionmentioning
confidence: 99%
“…This disagreement in projected changes between models highlights the importance of considering projections from a model ensemble rather than a single model. In addition, even if more of the cyclones that form in the future are more intense, the overall frequency of cyclones is most often predicted to stay the same or drop (Sobel et al., 2021). This means that the absolute frequency of intense cyclones may not rise, depending on how much overall cyclone frequency changes.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that the observed TCF change in several coastal regions over the past 40 years is likely associated with anthropogenic climate change, mainly through regional warming and its remote influence on circulations that changes the TC genesis and steering conditions. Many studies have focused on the global-and basin-mean change of TC activity 4,14,36 . However, considering the real threat posed by TCs, the TCF changes in coastal regions are perhaps our ultimate concern.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Another potential application of our methods is catastrophe modeling under climate change. Tropical cyclones pose a pressing problem for coastal communities, and have motivated several hybrid dynamical/statistical downscaling methods to project risk into the future under various climate change scenarios (Camargo et al, 2014;Lee et al, 2018;Jing & Lin, 2020;Sobel et al, 2021). Extreme precipitation of many varieties threatens cities and agriculture and is expected to change significantly with global warming (e.g., O'Gorman, 2012;Pfahl et al, 2017).…”
Section: Discussionmentioning
confidence: 99%